The hammer and the dance of cell cycle control (2020)
Cell cycle checkpoints secure ordered progression from one cell cycle phase to the next. They are important to signal cell stress and DNA lesions and to stop cell cycle progression when severe problems occur. Recent work suggests, however, that the cell cycle control machinery responds in more subtle and sophisticated ways when cells are faced with naturally occurring challenges, such as replication impediments associated with endogenous replication stress. Instead of following a stop and go approach, cells use fine-tuned deceleration and brake release mechanisms under the control of ataxia telangiectasia and Rad3-related protein kinase (ATR) and checkpoint kinase 1 (CHK1) to more flexibly adapt their cell cycle program to changing conditions. We highlight emerging examples of such intrinsic cell cycle checkpoint regulation and discuss their physiological and clinical relevance.